A novel 55-basepair deletion of hydroxymethylbilane synthase gene found in a Chinese patient with acute intermittent porphyria and her family: A case report. Issue 37 (September 2018) - Ren, Yi; Xu, Lin-Xin; Liu, Yun-Feng; Xiang, Chen-Yu; Gao, Fei; Wang, Yan; Bai, Tao; Yin, Jian-Hong; Zhao, Yang-Lu; Yang, Jing
Abstract: Rationale: Acute intermittent porphyria (AIP) is caused by hydroxymethylbilane synthase (HMBS) gene mutation. Patient concerns: A Chinese female patient with very typical AIP symptoms of severe abdominal pain, seizures, hypertension, and tachycardia, accompanied with hyponatremia, anemia, and hyperbilirubinemia. Diagnoses: She was diagnosed as AIP based on positive result of urine porphobilinogen and her clinical syndrome. Interventions: The proband was treated with intravenous glucose (at least 250 g per day) for 4 days. HMBS mutation was investigated in this family by Sanger sequencing. Outcomes: A heterozygous mutation of the HMBS gene was identified in the proband and 7 other family members. Genetic sequencing showed a deletion of 55 basepairs (C.1078_1132delGCCCATTAACTGGTTTGTGGGGCACAGATGCCTGGGTTGCTGCTGTCCAGTGCCT) including the stop codon position, leading to frameshift mutation. The mutation has not been documented in current gene databases. Further prediction of mutated protein structure suggests that the mutation is likely to produce prolonged peptide with structural change and less stability. Lessons: Physicians should pay attention to AIP attack in patients with suspected symptoms and make use of genetic testing to increase identification of mutated HMBS gene carriers for further preventive strategy.